The effect of mechanical and physical properties of chitosan / polyvinyl alcohol (PVA) blend films / Nur Razyatul Anisah Mohd Zaini - Mohd Zaini, Nur Razyatul Anisah (2020)
This study focused on film based Chitosan (CS)/ Polyvinyl Alcohol (PVA). The films were prepared by solvent casting method. CS/PVA blend films solution were produced then casted into petri dish before being dried in an oven until a finely thin film formed. Range of thin film thickness from 0.12mm to 0.20mm was being tabulated. Mechanical, physical and characterization were conducted. FTIR spectrum is used to identify the peak changes occurring among PVA and chitosan. From the characterization with FTIR, different peak occur from 3284.44 cm-1 to 3280.52 cm-1 after added the chitosan. The OH group of the blend film was reduced due to the presence of OH stretching vibration of PVA with the secondary NH group of chitosan. The tensile were carried out by using PVA filled with chitosan powder. From the result obtained, 40/60 CS/PVA blend film has the highest tensile strength which is 28.26 MPa, while 100% PVA has highest elongation at break which is 100.90%. The percentage of water absorption increase 1.4% with the addition of chitosan as filler. Thus, it is conclude that 40/60 CS/PVA have the best tensile strength among those loadings which have been reported in this study and can be improve by addition of coupling agent for better mechanical properties.